2021
DOI: 10.1111/jfbc.13911
|View full text |Cite
|
Sign up to set email alerts
|

A review on the fruit components affecting uric acid level and their underlying mechanisms

Abstract: Uric acid (UA) is produced in the liver and excreted through the kidneys and intestines. If UA is overproduced or its excretion reduces, the concentration of UA increases, leading to hyperuricemia and gout. The high concentration of UA is also related to cardiovascular disease, hypertension, obesity, and other diseases. Fruits are healthy foods. However, fruits contain fructose and small amounts of purine, and the product of their metabolism is UA. Therefore, theoretically, eating fruits will increase the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 102 publications
2
12
1
5
Order By: Relevance
“…Furthermore, dietary carbohydrate and fiber intake were negatively correlated with sUA levels. Consistent with our findings, a study of American adults showed that higher total dietary fiber intake was associated with a lower incidence of HUA [15]. According to the results of interaction analysis, the relationship of dietary fiber intake with sUA was significantly different in different gender.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, dietary carbohydrate and fiber intake were negatively correlated with sUA levels. Consistent with our findings, a study of American adults showed that higher total dietary fiber intake was associated with a lower incidence of HUA [15]. According to the results of interaction analysis, the relationship of dietary fiber intake with sUA was significantly different in different gender.…”
Section: Discussionsupporting
confidence: 90%
“…As for the mechanism, the viscosity and volume of dietary fiber will hinder the absorption of purines by the digestive system, and dietary fiber delays the digestion process of fructose and slows down the rate of reabsorption in the small intestine. In addition, dietary fiber can aid free bowel movement and promote the excretion of UA in the intestine [15][16][17]. However, no statistical difference was found in the associations of dietary intake of total sugars with sUA levels in our study.…”
Section: Discussioncontrasting
confidence: 73%
“…These ingredients are beneficial for disease prevention and management ( 49 52 ). The association between fruit and uric acid/gout is disputed, since fructose metabolism generated urates, and fresh fruit is high in fructose ( 53 , 54 ). Some studies have also found that fruit intake reduces the risk of gout because fruits contribute to urine alkalization and promote uric acid excretion ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Non-flavonoids compounds include phenolic acids, stilbenes, lignans, and curcuminoids. Flavonoids can be divided into flavanones, flavonols, flavanols, flavones, anthocyanins, and isoflavones (Zou et al, 2021).…”
Section: Effect and Mechanism Of Food Polyphenols In Treating Gouty Arthritismentioning
confidence: 99%